Technique of Excision of Double Head Pterygium with Conjunctival Autograft from both Eyes - Rosul, Md. Golam; Muna, Amena Binte Yusuf; Jahan, Tarana; Mahmud, Shahriar; Tussie, Rumana (Journal of Monno Medical College, 2024)
Background: Pterygium is not just a degenerative disease, but may be a proliferative disorder of the ocular surface. Objective: The aim of this study was to describe a technique of conjunctival autograft from both eyes for primary double head pterygium and evaluate its post operative result. Methodology: This retrospective study was conducted in the department of Ophthalmology at Monno Medical College, Manikganj, Bangladesh from July 2022 to December 2022 for duration of six months. After fulfill the selection criteria underwent conjunctival autograft from both eyes. Primary outcome measure was recurrence rate, graft retraction, Tenon's granuloma, dellen formation. Results: The highest patients belong to 35 to 45 years age group is about 18(60.0%) in this study. The number of male patients was 10 and that of female patient 20. There was no recurrence in this study. However, there were postoperative oedema (6.66%), sub-conjunctival haemorrhage (63.33%), graft retraction (20.0%), dellen (0.0%), Tenon’s granuloma (10.0%). Conclusion: In conclusion conjunctival autograft from both eyes appears to be successful technique with 0 recurrence rate in treating double head pterygium. Journal of Monno Medical College June, 2024;10 (1):03-06